Family caregiver frailty in adult congenital heart disease is overlooked: A call to action - Arianna Magon; Serena Francesca Flocco; Laura Schianchi; Massimo Chessa; Daniele Ciofi; Salvatore Angileri; Maddalena De Maria; Gianluca Conte; Silvia Favilli; Cristina Arrigoni; Rosario Caruso (International Journal of Cardiology Congenital Heart Disease)
The frailty of family caregivers (FCs) of adults with congenital heart disease (CHD) is an underrecognized yet critical issue in healthcare. As individuals with CHD live longer, their FCs, often aging alongside them, face escalating physical, emotional, and psychological challenges. This brief report examines frailty in FCs as a multidimensional issue stemming from prolonged caregiving demands and cumulative stress. The evidence gathered in this regard identifies three key domains affecting FCs: psychological stress and childcare, physical health decline, and the challenges of caregiving during transitions to adulthood. These findings underscore the urgent need for family-centered care models that incorporate tailored frailty assessments and targeted interventions to support FCs throughout their caregiving journey. Addressing caregiver frailty could improve outcomes for both patients and caregivers, strengthen resilience, and optimize resource allocation. This perspective calls for immediate action in research and policy to prioritize caregiver well-being in transition care programs, enhancing the quality of life for both caregivers and patients.